Determination of the features of integrated design of civil long-range aircraft with transonic truss-braced wing at the preliminary design stage - Pelykh, Valentyn; Andryushchenko, Volodymyr (Technology audit and production reserves, 2024)
The object of research is a civil mainline aircraft with a transonic truss-braced wing. The problem of designing an aircraft of this scheme at the preliminary design stage is being solved in the work. The results of the work include the concept of designing aircraft with a transonic truss-braced wing, the main advantages of such a scheme, the process of determining the geometric parameters of the truss-braced, features of the preliminary design of an aircraft with an extremely high aspect ratio truss-braced wing, possible approaches to the arrangement of units and their mutual arrangement. The results are explained by the difference in the design model (the cantilever beam is replaced by a beam on two supports) in mass analysis and the increased wing aspect ratio in aerodynamic calculation. The final data are based on a statistical study to determine the basic geometric parameters of assemblies of modern mainline passenger aircraft, synthesis of parameters of analog aircraft. For example, an aircraft capable of carrying 250 passengers over a distance of 13.000 km is considered. In the design process, values of aspect ratio, taper ratio, wing area, vertical tail and horizontal tail area ratio, and fuselage dimensions are accepted. Drawings of the general appearance of the aircraft have been developed and, based on it, a master geometry of the theoretical contour has been constructed. Graphs of first-order polar and maximum lift-to-drag ratio have been plotted, the reduction of aerodynamic drag in percentage terms has been determined, and the increase in aerodynamic lift-to-drag ratio in percentage terms for an aircraft with an extremely high aspect ratio truss-braced wing compared to similar characteristics of an aircraft with a conventional non-braced wing has been calculated. The approximate mass savings when using a truss-braced wing on the aircraft are determined in percentage terms. The expediency of using wings of greater aspect ratio, than modern aircraft currently have, has been justified. The expediency of using a brace for the aircraft with an extremely high aspect ratio wing has been justified. The obtained results can be used in practice in the process of developing the preliminary design of an aircraft with a truss-braced wing or in the modifications of existing aircraft to increase their fuel efficiency or increase the durability of wing elements due to reduced loads acting on them.